2014
DOI: 10.3109/09513590.2014.943722
|View full text |Cite
|
Sign up to set email alerts
|

Affective temperaments in pregnancy

Abstract: The third trimester of pregnancy is associated with significantly lower affective temperament. Future studies may help to understand the biological background of the present findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 33 publications
(48 reference statements)
3
0
1
Order By: Relevance
“…A novel finding of our study was that women with comorbid PMDD had an earlier age at menarche, and perhaps more importantly, the age of onset of BD was closer to the menarche in women with PMDD compared to those without PMDD. Previous smaller studies have supported an association between onset of BD and menarche , and if our result is replicated in an independent large study this may open a venue for research on the role of hormones/puberty on the onset of BD.…”
Section: Discussionsupporting
confidence: 79%
“…A novel finding of our study was that women with comorbid PMDD had an earlier age at menarche, and perhaps more importantly, the age of onset of BD was closer to the menarche in women with PMDD compared to those without PMDD. Previous smaller studies have supported an association between onset of BD and menarche , and if our result is replicated in an independent large study this may open a venue for research on the role of hormones/puberty on the onset of BD.…”
Section: Discussionsupporting
confidence: 79%
“…We found that having CT was related to having a lower level of educational attainment. This was also reported by Yazici et al (2014), who found CT to be related to lower educational level in young pregnant women. We also found a lower likelihood of employment, and an increase in somatic and psychiatric morbidity in both the participants and their first-degree relatives.…”
Section: Discussionsupporting
confidence: 78%
“…Anxious, cyclothymic, depressive, and irritable temperaments were found to be related to more dysfunctional sleep patterns during the perinatal period [ 44 ]. Pregnancy seems to independently and negatively predict irritable, anxious, and cyclothymic temperament [ 45 ]; our results on the PHQ-9 ≤4 group are consistent with these findings.…”
Section: Discussionsupporting
confidence: 89%